Are memories for sexually traumatic events "special"? A within-subjects investigation of trauma and memory in a clinical sample - Peace, Kristine; Porter, Stephen; Brinke, Leanne ten (My University, 2008)
According to a long-standing clinical tradition, sexually traumatic experiences are processed and recalled differently from other experiences, often leading to memory impairment. In this study, we compared the characteristics of traumatic memories for sexual violence and two other types of emotional experiences. N=44 women recruited from a local sexual trauma agency were asked to recall and describe three autobiographical events: sexual abuse/assault, a non-sexual trauma, and a positive emotional event. The characteristics of the three memory types were compared on both subjective and objective measures. Further, the potential influences of level of traumatic impact and dissociation were assessed. Results indicated that memories for sexual trauma were not impaired or fragmented relative to other memories. Instead, memories for sexual trauma were associated with a remarkably high level of vividness, detail, and sensory components. Further, high levels of traumatic impact were not associated with memory impairment. Implications for the ongoing traumatic memory debate are discussed.
Keywords: sex crimes; emotional trauma; memory disorders; sexual abuse victims; traumatic shock; posttraumatic stress disorder; PTSD